BLENDED LEARNING APPROACH INITIATING APPLICATION IN PRIMARY SCHOOL - Suhartono, Suhartono (Universitas Negeri Semarang, 2017)
Learning-face by the majority of primary school students considered unattractive. Instructional media such as books, globes, and other students are learning in the classroom, in different versions can be accessed by students quickly and easily on the internet. Instructional media on the Internet are generally formatted more attractively, can be studied interactively, and a variety of media types. This condition should inspire teachers to innovate in the classroom learning the material has promised. Innovation is intended to accommodate a penchant for students to access the internet outside of the classroom and put them in to-face learning in the classroom. Forms of this innovation is called the blended learning approach. There are two models of blended learning, which is a model on-line or hybrid learning) for primary school students are already familiar with computers and the Internet are familiar with off-line and blended learning for the students basic sekoalah not familiar with the Internet (rural). With these two models indicate that blended learning can be implemented in primary schools both to schools that are already connected to the Internet or not. With blended learning is expected students to learn independently, learning to be interesting (in accordance with a penchant for students to access the internet) and meaningful (using various online media).